Avatar: the last airbender - smoke and shadow, part one ebook - Yang, Gene Luen (Avatar: The Last Airbender,, 2015)
The Fire Nation is threatened by a prophecy told by the Kemurikage—mysterious figures thought only to exist in legend—remove Zuko from the throne or the country will perish! Avatar Aang and his friends escort Zuko and his family back to the capitol completely unaware of the looming threat growing in the city. Unrest is brewing as the New Ozai Society prepares to make its move against the crown, and children begin to go missing from their homes under mysterious circumstances! Written and drawn by the creative team behind the best-selling The Promise , The Search and The Rift , Gene Luen Yang and Gurihiru, in collaboration with Avatar: The Last Airbender and Legend of Korra creators Michael Dante DiMartino and Bryan Konietzko, this is the ultimate continuation of Avatar and the perfect companion to Legend of Korra !